The Effect of Teacher’s Pedagogical Knowledge on Class Management in Elementary Schools In Sanden Distric - Purbani Dwi Susanti; Lisa Retnasari (Jurnal Sekolah Dasar, 2021)
This research is motivated by the lack of optimal classroom management carried out by the teacher. The teacher has mastered the material (content) well, it's just that the delivery method is not optimal, in this case pedagogical knowledge of teaching, understanding of how certain problem topics are presented, adjusted to the various interests and abilities of students, and ways to make it understandable by learners. The purpose of this study was to determine the effect of teacher pedagogical knowledge on classroom management in elementary schools in Sanden District. This study uses a quantitative approach. The type used is ex-post facto research.The research design used to be Causal Research, this design was used to determine the effect of Pedagogical Knowledge on Classroom Management. The results of data collection will be calculated using SPSS. The results of this study indicate that there is an influence between the independent variable, namely Pedagogical Knowledge, on the dependent variable, namely Class Management. After calculating the t value, it is known that the tcount value is 3.104> 2.014, so it can be concluded that the Pedagogical Knowledge (X) variable has an effect on the Class Management variable (Y). This means that the higher the level of teacher knowledge related to pedagogical knowledge, the higher the level of classroom management